Immuno-modulatory functions of the type-3 secretion system and impacts on the pulmonary host defense: A role for ExoS of Pseudomonas aeruginosa in cystic fibrosis. (1st March 2018) - Belmadi, Nawal; Wu, Yongzheng; Touqui, Lhousseine
Abstract: Number of previous reviews had described the structures and the various functions of the exotoxins produced by the type-3 secretion system of Pseudomonas aeruginosa and their roles in the interactions of this bacterium with host cells. In this review, we summarize some relevant data of literature on ExoS, an exotoxin from the type-3 secretion system of P. aeruginosa, with a particular focus on the role of this toxin in the airways innate response of the host to infection by this bacterium, and its implication in the elimination of Staphylococcus aureus from the airways of patients with cystic fibrosis. Highlights: Type-3 secretion system modulates host defense in cystic fibrosis.